Architecture : form, space, & order - Ching, Francis D. K., 1943- (Wiley, 2023)
"For more than forty years, the beautifully illustrated Architecture: Form, Space, and Order has served as the classic introduction to the basic vocabulary of architectural design. The updated and revised Fifth Edition features the fundamental elements of space and form, illustrated with many new precedents and discussions of the latest technology trends. It is designed to encourage critical thought in order to promote a more evocative understanding of architecture"--